Real-world incidence of patient-reported dyspnoea with ticagrelor. (October 2018) - Prosser, Adaire E.; Dawson, Jessica L.; Koo, KethLyn; O'Kane, Karen M.; Ward, Michael B.; Woodman, Richard J.; Mangoni, Arduino A.; Phillips, Cameron J.
Dyspnoea, a common and multifactorial symptom in patients with acute coronary syndrome, has been associated with lower quality of life and hospital readmission. Prescriber preference for antiplatelet therapy, the standard of care in this patient group, is shifting to ticagrelor due to mortality benefits demonstrated in trials compared with clopidogrel. In these trials, dyspnoea was more commonly reported in patients prescribed ticagrelor but the aetiology is still debated. An observational cohort study was conducted to quantify the rates and severity of dyspnoea reported in patients with acute coronary syndrome and newly prescribed ticagrelor compared with those prescribed clopidogrel. Dyspnoea was more commonly reported in patients prescribed ticagrelor at each follow up post-discharge ( p  = 0.016). Rates were higher than previously reported in clinical trials. In some patients, dyspnoea necessitated drug therapy change and was associated with readmission to hospital ( p  = 0.046). As ticagrelor is widely prescribed as a first-line antiplatelet agent for a range of patients with acute coronary syndrome, the incidence of dyspnoea in a generalized patient cohort may result in higher rates of drug discontinuation. This in turn could lead to higher rates of rehospitalisation and potential treatment failure than that reported from the controlled setting of a clinical trial.